INTRODUCING ENGLISH THROUGH SONGS - M. Sabiqul Huda (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2018)
Reading skill is English as a foreign language should be taught from an early age because the children can learn anything quickly. In Indonesia, English language has been taught in kindergarten in the form of local contents / extracurricular. Children are at an early age to be introduced about the English in a simple form. Song is the simple form to interest the children in Introducing English. In practicing this method; the teacher must be able to choose the right songs for his or her students. The song selected should match the theme that will be taught, who is also familiar songs, and lyrics should be clear. Thus, the children can enjoy the songs. Learning English through Songs can be enjoyable and fun. It cause, they give children feel good about the circumstance, consist with a lot of repetition, which is just learners look for sample text, and encourage harmony within oneself and within one group. So, the children are easy to remember the vocabulary by sing a song.